Hedonic Lifestyle And Social Interaction As A Moderating Variable of The Influence of Brand Ambassadors on Customer Satisfaction: Penelitian - Iwan Adinugroho; Johannes P. Kumagaya; Muhammad Aqshel Revinzky Nizar; Nersiwad; Hartono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to investigate the moderating role of hedonic lifestyle and social interaction in the relationship between brand ambassador use and customer satisfaction. Amidst intense global brand competition, selecting public figures as brand ambassadors has become a key strategy to increase consumer trust and satisfaction. However, the effectiveness of this strategy often depends on the psychographic and sociological characteristics of consumers themselves. Using a quantitative method with a survey approach on 350 respondents who use beauty products, the data were analyzed using Structural Equation Modeling (SEM). The results show that brand ambassadors have a positive and significant influence on customer satisfaction. Key findings reveal that social interaction significantly strengthens this influence, while hedonic lifestyle acts as an emotional catalyst that increases expectations and satisfaction with the brand. The implications of this study suggest that marketing managers should focus not only on the popularity of brand ambassadors, but also on the social ecosystem and lifestyle of the target audience to optimize long-term satisfaction.